Conservancies as a vehicle for achieving sustainable development : with reference to a case study in the Nyae-Nyae area of Eastern Otjozonjupa, Namibia - Raphaely, Talia (Department of Environmental and Geographical Science, 2014)
Bibliography: leaves 130-136.